A practical U-healthcare network with security and QoS - Huang, S.-Y.; Hung, C.-C.; Lee, C.-C. (Journal of Digital Information Management, 2011)
As a consequence of rapid technological development, the normally isolated medical sensor platform is gradually being integrated into networks. However, most ubiquitous or mobile health systems are lacking a system that combines both network security and QoS (Quality of Service). This paper investigates the possible security and QoS methods of a ubiquitous healthcare network platform in OSI (Open System Interconnections)-layers. This network platform is based on the Wireless Overlay Networks (WON) Bluetooth, 802.11 and 802.16 over IPv6 network, and provides a secure and stable U-healthcare platform by including the application of healthcare sensors with RFID, U-healthcare PDA, VoIPv6, falling detection, and patient orientation.
Keywords: Healthcare; IPv6 network; QoS; Security; Ubiquitous